Outcomes and Prognostic Factors for Adult Patients With Congenital Heart Disease Undergoing Primary or Reoperative Systemic Atrioventricular Valve Surgery. (May 2017) - Stephens, Elizabeth H.; Han, Jiho; Ginns, Jonathan; Rosenbaum, Marlon; Chai, Paul; Bacha, Emile; Kalfa, David
Background: Adults with congenital heart disease (ACHD) undergoing systemic atrioventricular valve (SAVV) surgery are a complex, understudied population. We assessed midterm outcomes and prognostic factors in ACHD undergoing SAVV surgery. Methods: We performed retrospective evaluation of ACHD undergoing SAVV surgery from January 2005 to February 2016: 14 (33%) patients with congenital mitral valve stenosis/regurgitation, 15 (35%) with atrioventricular septal defect (AVSD), and 14 (33%) with congenitally corrected transposition of the great arteries (ccTGA) with systemic tricuspid valve regurgitation. Adverse events were defined as mortality, reoperation on SAVV, and late more-than-moderate (> moderate) SAVV regurgitation. Statistical analysis was performed using Fisher's exact test and one-way analysis of variance as well as univariate and multivariate risk factor analysis. Results: Fifteen (35%) patients had preoperative systemic ventricular dysfunction, including 13 patients with ccTGA (93%, P < .001). Twenty-three (54%) patients underwent valve repair, 20 (47%) patients underwent replacement, and 20 (47%) patients underwent an associated procedure. Replacement was higher in patients with ccTGA (86%) than the other groups ( P < 0.01). Thirty-seven patients (91% of survivors) were free of significant SAVV regurgitation at last follow-up, with patients with AVSD having greater regurgitation grades compared to the other groups ( P < 0.01). In-hospital mortality, late mortality, late > moderate SAVV regurgitation, and SAVV reoperation rates were 5% (n = 2), 2% (n = 1), 9% (n = 3), and 7% (n = 3), respectively. On multivariate analysis, predischarge SAVV regurgitation grade was the only significant predictor of adverse events (odds ratio = 8.2, 95% confidence interval: 1.1-63.8, P = .045). Conclusion: Overall outcomes in this challenging population are good. The single factor associated with adverse events was predischarge SAVV regurgitation grade.